Diet of European Catfish in a Newly Invaded Region - Ferreira, Marco (2020)
Biological invasions are considered to be one of the leading causes of biodiversity loss worldwide. Freshwater ecosystems are amongst the most biodiverse, containing about 50% of the world’s known fish species but, ironically, are the most invaded ecosystems. In Portuguese freshwaters, there are currently 20 identified non-native fishes, arriving at an unprecedented rate of a new species every two years. A recent non-native is the European catfish Silurus glanis, a top predator native to Central and Eastern Europe, that arrived at the Lower Tagus (Portugal) circa 2006. This study compares the dietary habits of this top predator in two di erent habitats of the Lower Tagus in order to evaluate its potential impact. The stomach contents of 96 individuals were analyzed, 61 from the lotic environment and 35 from the lentic systems. A total of 66 stomachs contained prey items, 38 from the lotic and 28 from the lentic. Diet varied considerably between habitats, with shrimp and crayfish being the most abundant prey items in the lentic systems and shrimp and fish the most abundant prey items in the lotic section. Tendency to piscivory was observed in large-sized individuals. Overall, the findings in this study provide the first evidence of the potential impacts of European catfish through predation on the fish communities.